Knowledge mapping and trend identification in UAV-enabled hybrid FSO/RF communication systems - Kamran Ali Memon; Khalid H. Mohammadani; Abdul Ghaffar; Khurrum Karim Qureshi; Muhammad Mahmood Ali (Results in Engineering)
UAV-based Hybrid FSO/RF Communication Networks (UHCNs) enable wireless networks with dynamic coverage and adaptability by combining Free Space Optics (FSO), Radio Frequency (RF), and Unmanned Aerial Vehicle (UAV) technologies, making them crucial for 6G. With significant emergence and applications over the last decade, these networks face multifaceted challenges like switching mechanisms, security concerns, resource management, power and energy efficiency, which have encouraged the scientific community to produce a substantial volume of new findings/literature. However, existing literature lacks a quantitative assessment of research progress and emerging trends in UHCNs. This study utilized scientometric analysis to analyze and visualize five years of Web of Science (WoS) data. The analysis included co-citation, co-authorship, and co-occurrence networks to present the latest research trends and cutting-edge investigations in UHCNs. Knowledge clusters were systematically categorized, and key clusters in knowledge mapping were identified. The study employed several types of analysis. These included structural, visual, and temporal analysis based on citation frequency to trace the origins of UHCN research, its evolution, and its current state. It identified key works that significantly contributed to its development and emerging trends. The analysis encompassed 298 critical articles, 299 leading core authors, and 291 cited authors, spanned 08 knowledge domains/hotspots, highlighted 294 trending frontier keywords, and involved contributors from 63 countries, 300 research institutions, and 295 publishing journals. New research trends emphasize the need to design RIS-UAVs that use less energy, have open testbeds to test them in the real world, and standards for deploying autonomous UAVs safely and ethically. This study aims to facilitate interdisciplinary and multidisciplinary research and draw a significant audience from the academic and industrial communities involved in UHCN research.